Slow Larvae Mutant and Its Potential to Improve the Pupal Color-Based Genetic Sexing System in Mexican Fruit Fly, (Diptera: Tephritidae) - Meza, José S (J Econ Entomol, 2019)
For many years, an area-wide fruit fly control campaign against the Mexican fruit fly, Anastrepha ludens (Loew) has been implemented in some regions of Mexico and Texas, using the sterile insect technique (SIT) as its principal component. To improve the efficiency of the SIT, a genetic sexing strain based on black pupae mutation (bp) was developed for A. ludens, namely, ‘Tapachula-7’ (Tap-7 genetic sexing strains [GSSs]). This strain was introduced into the AW-IPM program recently and allows male-only releases for SIT applications. Here, we report the genetic and biological characterization of a new mutation, slow larvae (sl), which was introduced to the original translocation of the Tap-7 GSS resulting in two new GSS (slow-7 and Tap/slow-7). In both GSSs, the translocated wild-type males emerge from brown pupae that develop faster than females. The females are homozygous for sl mutation in the slow-7 GSS and homozygous for sl and bp mutations in the Tap/slow-7 GSS, reaching larval maturity 2 d after most of the wild-type males, allowing the separation of most males during pupariation. The potential use of the slow-7 and Tap/slow-7 GSSs in mass rearing and large-scale population suppression programs is discussed.